CLINICAL EFFICACY OF IMMUNOTHERAPY IN THE TREATMENT OF ATOPIC DERMATITIS IN CHILDREN - Нематова Х. Г.; Юлдашов И. Р. (Web of Journals Publishing, 2025)
The article presents the results of a study devoted to the optimization of the clinical efficacy of complex therapy for children with exacerbation of IgE-mediated atopic dermatitis by including an immunomodulator of microbial origin - glucosaminylmuramyl dipeptide.
Keywords: Atopic dermatitis, traditional therapy, immunotherapy, muramyl dipeptides, clinical efficacy, lycopid.